What determines uptake of pertussis vaccine in pregnancy? A cross sectional survey in an ethnically diverse population of pregnant women in London. Issue 43 (26th October 2015) - Donaldson, Beverly; Jain, Prerna; Holder, Beth S.; Lindsey, Benjamin; Regan, Lesley; Kampmann, Beate
Highlights: Uptake of pertussis vaccine in pregnancy in our population was only 26%. Although nationally recommended, only 63% of pregnant women interviewed were even aware of the pertussis vaccination programme. Lack of encouragement from healthcare professionals was identified as the main reason. 91% of women believed healthcare professionals need to become more engaged in providing timely information about vaccines in pregnancy. Abstract: Introduction: Following the major outbreak of pertussis and 14 infant deaths across England in 2012, the Department of Health (DH) introduced the UK's first maternal pertussis vaccination programme. Data published by Public Health England (PHE) suggest uptake of the vaccine varies considerably across the country. The reasons for this heterogeneity need to be addressed to optimise the impact of the programme. Objective: To assess uptake of antenatal pertussis and influenza vaccine in a leading NHS Trust in London and to explore awareness and attitudes of pregnant women towards the pertussis vaccination programme. Design: A cross sectional survey was conducted in an ethnically diverse group of 200 pregnant women accessing antenatal care at Imperial Healthcare NHS Trust. Quantitative data was tabulated and content analysis was carried out on the free text. Qualitative data was divided into themes for accepting or declining the vaccine. Results: Awareness of the programme was 63% (126/200) with actual uptake of the vaccine only 26.0% (52/200). Women had received information from multiple sources, primarily General Practitioners (GP) and midwives. 34.0% (68/200) of women were offered the vaccine at their GP practice, only 24% reported a meaningful discussion with their GP about it. Uptake differed by up to 15.0% between ethnicities. Qualitative data showed that uptake could be significantly enhanced if vaccination was recommended by a familiar healthcare professional. Feeling uninformed, lack of professional encouragement and uncertainties of risk and benefit of the vaccine were the greatest barriers to uptake. Conclusion: Vaccine uptake in this cohort of pregnant women was poor. Understanding the target audience and engaging with key groups who influence women's decision-making is essential. Knowledgeable health care professionals need to recommend the vaccine and provide accurate and timely information to increase success of this important programme.